Pendampingan dan Pelatihan Penggunaan E-Government Pada Pelayanan Publik Di Kelurahan Malalayang Satu Barat Kota Manado - Jericho Pombengi; Johny Hanny Posumah; Jones Tompodung (WINDRADI: Jurnal Pengabdian Masyarakat, 2025)
The utilization of information and communication technology (ICT) in public administration is a strategic step to promote good governance. Since the issuance of Presidential Instruction No. 6 of 2001 on Telematics, the Indonesian government has encouraged the implementation of e-Government across various regions. However, its application at the village level still encounters several challenges, including limited community understanding, low digital literacy, and inefficiencies in public service delivery. This community engagement program was conducted in Malalayang Satu Barat Village, Manado City, North Sulawesi, with the primary goal of enhancing public awareness of e-Government as a tool for service digitalization. The methods applied included needs assessment surveys, counseling, mentoring, and participatory training involving local residents. The results indicate improved community understanding of e-Government, particularly in accessing information, reducing dependence on direct visits to the village office, and fostering awareness of environmental management and public health issues. The benefits of the program extend beyond digital literacy improvement, contributing to the strengthening of social capital and encouraging active community participation. These findings highlight the significance of community-based approaches in supporting the effective implementation of e-Government at the local level.